RETINAL OXIMETRY IS ALTERED IN EYES WITH CHOROIDAL MELANOMA BUT NOT IN EYES WITH CHOROIDAL NEVI. Issue 11 (November 2020) - Brouwer, Niels J.; Marinkovic, Marina; Bleeker, Jaco C.; el Filali, Mariam; Stefansson, Einar; Luyten, Gregorius P. M.; Jager, Martine J.
Abstract : Purpose: To compare retinal vessel oxygenation in eyes with an untreated choroidal nevus or choroidal melanoma. Methods: The affected and fellow eye of patients with an untreated choroidal nevus (n = 42) or choroidal melanoma (n = 45) were investigated using noninvasive retinal oximetry (Oxymap T1). Oxygen saturation of arterioles (ArtSat) and venules (VenSat) was determined, together with the arteriovenous difference (AV-difference). Results: In choroidal nevus patients, retinal oximetry did not differ between the affected and fellow eye: the mean ArtSat was 94.5% and 94.2% ( P = 0.56), the VenSat was 60.5% and 61.3% ( P = 0.35), and the AV-difference was 34.0% and 32.9% ( P = 0.18), respectively. In choroidal melanoma patients, alterations were detected: the mean ArtSat was 94.8% and 93.2% ( P = 0.006), the VenSat was 58.0% and 60.0% ( P = 0.014), and the AV-difference was 36.8% and 33.2% ( P < 0.001), respectively. The largest increase in AV-difference was observed between the retinal halves without the lesion in melanoma eyes compared with the corresponding half in the fellow eye (37.5% vs. 32.1%, P < 0.001). Conclusion: Although retinal oximetry was not significantly altered in eyes with a choroidal nevus, eyes with choroidal melanoma showed an increased ArtSat and decreased VenSat, leading to an increased AV-difference. These changes may be caused by inflammation and a higher metabolism, with larger oxygen consumption, leading to altered blood flow and intraocular oxygen relocation. Abstract : Supplemental Digital Content is Available in the Text.Noninvasive retinal oximetry demonstrates alterations in eyes with untreated choroidal melanoma, including an increased difference between arterial and venous saturation. These changes were not observed in eyes with choroidal nevi and may be related to the tumour's metabolism or inflammatory changes.